2000
DOI: 10.1007/s004020050462
|View full text |Cite
|
Sign up to set email alerts
|

The influence of obesity on perioperative morbidity and mortality in revision total hip arthroplasty

Abstract: The significance of obesity as a risk factor for postoperative complications was determined in a consecutive series of 229 cases of revision total hip replacement. The body mass index (BMI) was used as an objective measure to classify the patients. The group-wise analysis of data included all medical and procedure-related complications, the number of fatal cases, operative time, requirement for analgesics, the number of transfusions and perioperative haemoglobin levels. The results of our study demonstrate a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 17 publications
2
48
1
5
Order By: Relevance
“…Despite the increasing prevalence of obesity among patients undergoing THA, there are few studies examining the potential financial implications of obesity in this patient population [4,10,14,19,21,33]. We therefore examined the association between BMI and length of stay and costs taking into account obesity-related comorbidities and short-term THA complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the increasing prevalence of obesity among patients undergoing THA, there are few studies examining the potential financial implications of obesity in this patient population [4,10,14,19,21,33]. We therefore examined the association between BMI and length of stay and costs taking into account obesity-related comorbidities and short-term THA complications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a large-scale study [15] included 35,000 orthopaedic surgeries and the length of stay was 1.1 days longer for morbidly obese patients, but it has been difficult to show this association in previous THA studies [4,10,14,19,21,33]. We believe this is a result of methodologic issues, including small sample sizes, power, measurement of obesity, and cost outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients in between these two values were not included in the study [7]. Another study of 229 patients by Perka et al [13] reported overweight patients had an increased operative time in revision hip surgery but no other increase in perioperative complications. Long-term outcomes were not reported [13].…”
Section: Discussionmentioning
confidence: 99%